A multifunctional oxidosqualene cyclase from Tripterygium regelii that produces both α- and β-amyrin. Issue 42 (27th June 2018) - Lu, Yun; Zhou, Jiawei; Hu, Tianyuan; Zhang, Yifeng; Su, Ping; Wang, Jiadian; Gao, Wei; Huang, Luqi
Abstract : A multifunctional oxidosqualene cyclase was cloned from Tripterygium regelii and identified as a mixed-amyrin synthase, which can produce both α- and β-amyrin. Abstract : Tripterygium regelii is a rich source of triterpenoids, containing many types of triterpenes with high chemical diversity and interesting pharmacological properties. The cDNA of the multifunctional oxidosqualene cyclase ( TrOSC, GenBank accession number: MH161182), consisting of a 2289 bp open reading frame and coding for 762 amino acids, was cloned from the stems and roots of Tripterygium regelii . Phylogenetic analysis using OSC genes from other plants suggested that TrOSC might be a mixed-amyrin synthase. The coding sequence was cloned into the expression vector pYES2 and transformed into the yeast Saccharomyces cerevisiae . The resulting products were analysed by GC-MS. Surprisingly, although it showed 76% sequence identity to lupeol synthase from Ricinus communis, TrOSC was found to be a multifunctional triterpene synthase producing both α- and β-amyrin, the precursors of ursane and oleanane type triterpenes, respectively. qRT-PCR analysis revealed that the transcript of TrOSC accumulated mainly in roots and stems. Taken together, our findings contribute to the knowledge of key genes in the pentacyclic triterpene biosynthesis pathway.